Case report: Favipiravir-induced bluish corneal discoloration in infant with COVID-19 - Jiravisitkul, Paveewan; Thonginnetra, Saraiorn; Wongvisavavit, Rintra (Frontiers in Pediatrics, 2023)
This report describes a case of a male infant diagnosed with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection who was prescribed favipiravir therapy. The mother noticed a discoloration of the child’s eyes within 18 hours of therapy, and the cornea returned to normal color within 5 days of medication cessation. This case report highlights the need for monitoring of favipiravir therapy in children due to the potential side effect of corneal discoloration, which has not yet had its long-term effects identified.